Effects of tip clearance height on hot-streak migration in high subsonic micro turbine - Jingde Zhu; Xin Xiang; Xiaoan Hu; Chen Xia (Case Studies in Thermal Engineering, 2023)
An intimate understanding of the temperature distribution of turbine components is required for advanced and efficient cooling systems and blade designs. Regarding the micro turbine, the stronger tip-leakage flow caused by the dimensional effect has a non-negligible impact on the flow structure in the rotor, which can modify the hot-streak migration and its influence on the turbine. In this study, a numerical simulation is performed on a 1-stage high subsonic micro axial turbine to investigate the effect of tip-clearance height on hot-streak migration. The results show that, in the micro rotor, the relative radial hot-streak migration (towards the blade tip) caused by tip leakage exists a linear relationship between this migration and the clearance height within limits. The hot-streak migration at the blade tip is influenced by the changing of leakage flow and induced vortex, which will change the temperature distribution on the blade surface and tip area. The increase of clearance height will magnify the range of the relative total temperature fluctuation at the rotor-blade surface. An increase of 4.8%h for clearance will lead to an increase of 53.3% (10.4 K from 19.5 K) for the range of the fluctuation.